Building Sustainable Organizational Performance through Strategic HRM, Knowledge Management, and Sharia Economic Governance: Empirical Evidence from the Ministry of Religious Affairs (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This study aims to examine the influence of Strategic Human Resource Management (SHRM), Knowledge Management, and Sharia Economic Governance on Sustainable Organizational Performance within the Ministry of Religious Affairs, Semarang Regency. Using a quantitative approach, data were collected from 100 employees as respondents through structured questionnaires. The research employed multiple regression analysis using SPSS to test the proposed hypotheses. The findings reveal that SHRM significantly contributes to improving organizational effectiveness through strategic alignment of human resources. Knowledge Management enhances innovation and institutional learning, while Sharia Economic Governance strengthens ethical decision-making and transparency within the organization. Together, these three dimensions form an integrated framework that supports long-term sustainability and organizational excellence. The study contributes to the development of Islamic-based strategic management models in public institutions and highlights the importance of combining managerial, intellectual, and ethical dimensions in achieving sustainable organizational performance.
Keywords: Strategic Human Resource Management; Knowledge Management; Sharia Economic Governance; Sustainable Organizational Performance; Ministry of Religious Affairs